Women Empowerment in Higher Education in Nepal - Koirala, Padma (Interdisciplinary Research in Education, 2023)
This paper attempts to address women's empowerment in higher education in Nepal. This is a review paper based on a systematic review of women's empowerment through education. The dictionary definition of empowerment refers to giving power and status to an individual or group in a particular situation. Empowerment enables them to increase access to opportunities without limitations, such as in education, profession, and lifestyle. This paper uses a systematic review method to focus on the role of education in women's empowerment. For this purpose, nine articles were selected for systematic review from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses [PRISMA] model. The review materials that focused on the different dimensions of women’s empowerment, both theoretically and methodologically, were considered for systematic review. The systematic review results reveal that education is a precondition for women’s empowerment. However, most of the conclusions were based on census data covering women’s literacy rates, and their findings did not explicitly mention the indicators of women’s studies. Only a few studies assessed the dimensions of women’s empowerment, such as personal, economic, social, and political dimensions.